Oral Administration of Polypodium leucotomos Powder Inhibited Sunburn Cells Formation in UVB-Induced Male Wistar Rats (Rattus Norvegicus) - Priskila Ariana; I Gusti Made Aman; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: UVB can cause direct damage to the DNA and eventually cause apoptosis of epidermal keratinocytes, which is called a sunburn cells. Polypodium leucotomos (Heliocare®) is one of the skin photoprotectors that can modulate immune and inflammatory responses that play a role in preventing sunburn. This study aimed to prove that oral administration of Polypodium leucotomos powder inhibits sunburn cells formation in UVB-induced male Wistar rats (Rattus norvegicus). Methods: This study was a true experimental study using post-test only control group design consisted of two groups with 18 rats/group. One group as a control group (P0) that was treated with oral 1ml aquadest (force feeding) for 10 days. The other group was the treatment group (P1) treated with oral Heliocare® dry powder (Polypodium leucotomos) of 80 mg/kg BW diluted in 1 ml aquadest (force feeding) for 10 days. On the day 11, the dorsal skin was shaved and exposed to single dose UVB of 25mJ. Twenty-four hours later, rats were sacrificed and skin samples were collected for histology preparations with Hematoxylin-Eosin staining and sunburn cells were counted as posttest data. Results: The results showed that the average number of sunburn cells in the P0 group was 36.5±7.53 sunburn cells/mm2, while in the P1 group was 8.3±3.59 sunburn cells/mm2 (p <0.05). Those data showed that there was a significant different of average number of sunburn cells among group tested. Conclusion: It can be concluded that oral administration of 80 mg/kg BW Polypodium leucotomos powder inhibited sunburn cells formation in UVB-induced male Wistar rats (Rattus norvegicus).